Search for the standard model Higgs boson in the decay channel H→ZZ→4ℓ in pp collisions at √s=7 TeV. - Chatrchyan, S; Khachatryan, V; Sirunyan, A; Tumasyan, A; Adam, W; Bergauer, T; Dragicevic, M; Erö, J; Fabjan, C; Friedl, M; Frühwirth, R; Ghete, V; et al. (2012)
A search for a Higgs boson in the four-lepton decay channel H→ZZ, with each Z boson decaying to an electron or muon pair, is reported. The search covers Higgs boson mass hypotheses in the range of 110<m(h)<600 4.7="" an="" analysis="" are="" at="" by="" cms="" collisions="" corresponding="" data="" detector="" events="" fb(-1)="" four-lepton="" from="" gev.="" in="" integrated="" invariant="" lhc.="" luminosity="" m(4ℓ)="" mass="" observed="" of="" pp="" recorded="" seventy-two="" tev="" the="" to="" uses="" with="" √s="7">100 GeV (with 13 below 160 GeV), while 67.1±6.0 (9.5±1.3) events are expected from background. The four-lepton mass distribution is consistent with the expectation of standard model background production of ZZ pairs. Upper limits at 95% confidence level exclude the standard model Higgs boson in the ranges of 134-158 GeV, 180-305 GeV, and 340-465 GeV. Small excesses of events are observed around masses of 119, 126, and 320 GeV, making the observed limits weaker than expected in the absence of a signal.</m(h)<600>